2015
DOI: 10.3892/mmr.2015.4046
|View full text |Cite
|
Sign up to set email alerts
|

Combinational treatment with microRNA-133b and cetuximab has increased inhibitory effects on the growth and invasion of colorectal cancer cells by regulating EGFR

Abstract: Colorectal cancer (CRC) is the third most common cancer with a very poor prognosis predominantly due to its high rate of tumor invasion and migration, and its resistance to anti‑epidermal growth factor receptor (EGFR) therapy. Although CRC has been widely studied, the underlying molecular mechanism remains to be elucidated. MicroRNA (miR)‑133b has been demonstrated to act as a tumor suppressor in several human cancer types by regulating EGFR. However, the detailed involvement of miR‑133b and EGFR in CRC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The com- bination of miR-133b mimics with anti-EGFR mAb, exhibited stronger inhibitory effects on CRC cells than treatment with either alone. Thus, the study suggested that miR-133b enhanced the sensitivity to cetuximab, and the combination of miR-133b and cetuximab may be a potential treatment for CRC patients [65]. Similarly, an alike role was found on miR-7.…”
Section: Roles Of Mirnas In Egfr-targeted Therapy Resistancementioning
confidence: 69%
“…The com- bination of miR-133b mimics with anti-EGFR mAb, exhibited stronger inhibitory effects on CRC cells than treatment with either alone. Thus, the study suggested that miR-133b enhanced the sensitivity to cetuximab, and the combination of miR-133b and cetuximab may be a potential treatment for CRC patients [65]. Similarly, an alike role was found on miR-7.…”
Section: Roles Of Mirnas In Egfr-targeted Therapy Resistancementioning
confidence: 69%
“…The authors conclude that reintroduction of miR-143 or miR-145 might lead to resensitize CRC cells to cetuximab by stimulating cetuximab-dependent ADCC to induce cell apoptosis [ 43 ]. The possible interactions among miRNAs and anti-EGFR therapy was revealed also by Zhou et al In this study, combination treatment with miR-133b mimics and cetuximab, exhibited improved inhibitory effects on the growth and invasion of CRC cells compared with treatment with either alone [ 44 ].…”
Section: Non-coding Rna As Predictive Biomarkers Anti-egfr Monoclomentioning
confidence: 86%
“…Cell proliferation was determined using the Cell Proliferation Kit I (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) (Sigma, USA) as previously described [14]. Briefly, approximately 1×10 4 cells/well were grown in 96-well plates to 70–80% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…In gastric cancer, miR-133b acts as a tumor suppressor and negatively regulates FSCN1 expression [13]. Restoring the expression of miR-133b can inhibit the growth and invasion of colorectal cancer cells via directly targeting EGFR [14]. miR-133b can also significantly inhibit bladder cancer cell proliferation and apoptosis by targeting Bcl-w [15].…”
Section: Introductionmentioning
confidence: 99%